Analisis Dan Dampak Cash Flow Statement Terhadap Likuiditas Perusahaan PT Kimia Farma Tbk. - Ahmad Yani; Riska Putri Susanti (Otonomi, 2023)
This research is a research conducted by analyzing the Cash Flow Statement on the liquidity of the company PT Kimia Farma Tbk., by using the cash flow ratio of liquidity. The purpose of conducting this research is to analyze and describe cash flow statements on company liquidity at Kimia Farma Tbk. In 2020-2021. The results of this study are: (1) The ratio of operating cash flows in 2020 and 2021 is below 1, indicating that the company is not yet good where the company has not been able to pay its current obligations (2) The capital expenditure ratio in companies in 2020 and 2021 is the result in 2020 the company will experience difficulties in financing its capital expenditures, while in 2021 the company will be able to finance its capital expenditures (3) The total debt ratio of companies from 2020 to 2021 has decreased. This shows that the condition or performance of the company is not good, where the company has a poor ability to pay all its obligations (4) The ratio of Cash Coverage to Current Debt in companies in 2020 and 2021 companies seen at this ratio are in unfavorable conditions, where the company is unable to finance capital expenditures from the company's cash flow on investment. (5) The company's cash to interest coverage ratio in 2020 has yielded more than 1 time, indicating that the company's ability to pay interest on liabilities is good, while in 2021 it has yielded less than 1 time, indicating that the company's ability to pay interest on low liability. (6) The Fund Flow Coverage Ratio for companies in 2020 and 2021 results in the calculation of the ratio being more than 1 time. This shows that the company's profit every year tends to increase and is well proportional to the amount of the company's liabilities.